THE AUTHORITY OF THE ACEH GOVERNMENT IN THE FIELD OF MINERAL AND COAL MINING LICENSING IS BASED ON LAW NUMBER 11 OF 2006 CONCERNING ACEH GOVERNMENT - Rahima Kamariah; Ilyas Ismail; Ria Fitri (PT. Radja Intercontinental Publishing, 2024)
This research aims to explain the position of Aceh Province in the management of natural resources in the field of mineral and coal mining based on the specificities and privileges of Aceh, as well as to explain the authority of the central government in the field of mineral and coal mining as well as explain the authority of the Aceh government in terms of mineral and mining permits. coal in the Aceh Province area. This research is empirical legal research using a statutory approach and a legal sociology approach. The data sources used in this research are primary and secondary data using primary legal materials, secondary legal materials and tertiary legal materials, then the data obtained from both Secondary legal materials and tertiary legal materials will be analyzed. The results of the research show that the authority to manage mineral and coal mining in the Aceh Province area is managed by the Aceh government in accordance with statutory regulations, this authority is an attributive authority granted directly by Law Number 11 of 2006 concerning the Aceh Government, so that in terms of mineral mining and coal, the central government does not have full rights in controlling it because the central government's mining regulations exclude the Aceh government in its regulation, namely in article 137A of Law Number 3 of 2020 concerning amendments to Law Number 4 of 2009 concerning mineral and coal mining. The granting of special autonomy to Aceh, especially in the management of natural resources in the mineral and coal mining sector, has not been fully respected by the central government. It is recommended that the central government needs to pay attention to the authority possessed by the Aceh government as one of the special and special regions, as explained in the constitution that the Indonesian State recognizes and respects regional government units which are special and given special authority based on the principle of decentralization. , to create legal certainty in the management of mineral and coal mining in the special autonomous region of Aceh.